Comparison Between Conventional Design and Cathode Gas Recirculation Design of a Direct-Syngas Solid Oxide Fuel Cell–Gas Turbine Hybrid Systems Part I: Design Performance - Vahid Azami; Mortaza Yari (Center of Biomass & Renewable Energy, Diponegoro University, 2017)
In this paper, a conventional SOFC–GT hybrid system and a SOFC–GT hybrid system with cathode gas recirculation system fueled with syngas as the main source of energy were analyzed and their performances were compared. In the conventional SOFC–GT hybrid system, the incoming air to the cathode was heated at air recuperator and air preheater to meet the required cathode inlet temperature. In the SOFC–GT hybrid system with cathode gas recirculation, besides air recuperator and air preheater, the recirculation of the cathode exhaust gas was also used to meet the required cathode inlet temperature. The system performances have been analyzed by means of models developed with the computer program Cycle–Tempo. A complete model of the SOFC–GT hybrid system with these two configurations evaluated in terms of energy and exergy efficiencies and their performance characteristics were compared. Simulation results show that the electrical energy and exergy efficiencies achieved in the cathode gas recirculation plant (64.76% and 66.28%, respectively) are significantly higher than those obtained in the conventional plant (54.53% and 55.8%). Article History: Received Feb 23rd 2017; Received in revised form May 26th 2017; Accepted June 1st 2017; Available onlineHow to Cite This Article: Azami, V, and Yari, M. (2017) Comparison between conventional design and cathode gas recirculation design of a direct-syngas solid oxide fuel cell–gas turbine hybrid systems part I: Design performance. International Journal of Renewable Energy Development, 6(2), 127-136.https://doi.org/10.14710/ijred.6.2.127-136